Antibiotics for Preventing Recurrent Urinary Tract Infection: Systematic Review and Meta-analysis. (3rd July 2022) - Jent, Philipp; Berger, Julia; Kuhn, Annette; Trautner, Barbara W; Atkinson, Andrew; Marschall, Jonas
Abstract: Recurrent urinary tract infections are a common health problem. The only comprehensive synthesis on antibiotic prophylaxis in the last 15 years has been a guideline-embedded meta-analysis. We conducted a systematic review and meta-analysis of randomized controlled trials published up to October 13, 2020, evaluating patients age ≥12 years with either ≥2 episodes of lower urinary tract infection (UTI) within 6 months or ≥3 in the past year. Placebo or antibiotics were allowed as comparators. Study quality was low. In the 11 placebo-controlled trials, the risk for developing UTI was 85% lower with prophylaxis in comparison with placebo (risk ratio [RR], 0.15; 95% CI, 0.08–0.29). In the 9 head-to-head trials, the efficacy of the antibiotic agents appeared similar: The pooled RR indicated no difference between nitrofurantoin and comparators (RR, 1.01; 95% CI, 0.74–1.37), nor trimethoprim (+/- sulfamethoxazole; RR, 1.34; 95% CI, 0.89–2.03) or norfloxacin and comparators (RR, 1.17; 95% CI, 0.43–1.70). Studies comparing intermittent (postcoital) with continuous strategies revealed intermittent application to be equally effective.